Automatic crack of Yahoo CAPTCHA - Choudhary, Niket; Deshmukh, Sudarshan (International Journal of Computer Sciences and Engineering, 2015)
CAPTCHA is a security mechanism used to prevent bots from using the services of the website intended for humans. Till date, a number of CAPTCHA schemes have been successfully broken which made the design of CAPTCHAs an interesting area of research. Schemes of CAPTCHAs can be categorized as text based, image based, animation based, natural language based, option based and audio based. This paper explains some of the strengths and weaknesses of the CAPTCHA currently used by Yahoo and steps to crack it automatically. The CAPTCHA is an animation based text CAPTCHA. It is cracked by first removing the noise in the background and finally applying our own developed Optical Character Recognition (OCR) program which is specialized for reading characters in Yahoo CAPTCHA only. The automatic crack program has a successful rate of 63%.